Designing a Mobile Application Based on Gamification Method to Increase Muslims Reading Interest - Pratama, Arjun Bayu; Azhari, Muhammad Fikri (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2020)
This research was aimed to design mobile application based on gamification method as an effort to increase Muslims reading interest. This application is designed using a prototype method through several stages, namely determining the problem topic, designing the application as a solution to the problem, validating the application to the expert and ending with a test of the effectiveness of the application that has been designed. There are several features provided in the app's design including points, rewards, levels, badges, daily challenges, quests and leaderboards. All of the features available above are designed so that readers have direct communication with the app so that it becomes more interesting, it can even increase reading interest for users of this application. After an assessment of several users, overall stated that the gamification method with mobile app is very effective, interesting and also useful as a means of improving the reading and literacy of Muslims. The design of this application is a finding of digital technology creativity that has been successfully designed and can even be used, but this application still needs to be developed again so that it is more effective and innovative.